Prognostic factors for recurrence in acquired hemophilia A-results from a long-term observational study - Lisa Reich; Florian Gatzke; Steffen Rauchfuss; Stefanie Roth; Wolfgang Miesbach (Research and Practice in Thrombosis and Haemostasis)
Objectives: Acquired hemophilia A (AHA) is a rare autoimmune disease caused by autoantibodies against factor (F)VIII (FVIII), potentially leading to life-threatening bleeding. While predictors for remission have been analyzed, data on recurrence is lacking. Methods: This study investigated predictors of AHA recurrence in 41 patients. Patients were divided into 2 groups: those with recurrence (n = 18) and those in stable long-term remission (n = 23) with at least 1 year of follow-up. Results: All relapses occurred within 1 year of initial remission. The median follow-up period was 3.8 years (IQR, 1.8-6.4) for all included patients. Multivariate Cox regression analysis revealed that initial FVIII activity <1 IU/dL and failure to achieve initial complete remission (CR) were significant predictors of relapse. Kaplan–Meier curves showed significantly different relapse-free survival rates for patients with initial FVIII activity <1 IU/dL vs ≥1 IU/dL (χ2[1] = 5.950, P = .015), and for those achieving initial CR vs partial remission (χ2[1] = 6.570, P = .010).Other factors such as inhibitor titer, gender, age, World Health Organization scale, underlying disorder, controlled disorder, initial immunosuppressive therapy, immunosuppressive therapy escalation, and partial remission at day 21 showed no significant relation to recurrences. Overall survival did not differ significantly between relapsing and nonrelapsing patients (χ2[1] = .896, P = .344). Conclusion: Initial FVIII <1 IU/dL and failure to achieve initial CR are identified as risk factors for recurrence in AHA. Patients with these characteristics should be closely monitored for at least 1 year after initial remission due to increased recurrence risk.